Pengembangan Sistem Informasi Manajemen Percetakan pada Gajayana Digital Printing Kota Malang berbasis Website - Jovi Akbar Fandopa; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Management information system printing is a technology that must be owned in a company which involves the process of data management. The research was conducted at Gajayana Digital Printing Malang City which is engaged in printing services. Where the processes that occur in it have not fully used the management process, one example is the management of order data is still done manually because the storage of transaction data is only on the order note, including to calculate the total sales calculated based on the order note. To help the printing business, an application system is needed that has the main feature for storing data on ordering and purchasing printing products to make it easier to calculate the total sales and purchases. The information system application developed is web-based so that it can be accessed with various devices via a web browser. System development is carried out using the Waterfall method because the initial system requirements have been defined which are obtained through interviews with owner business. The system has 3 actors and a total of 37 functional requirements. The development is done using MERN Stack technology. The tests carried out apply unit testing using the white box method, and system validation testing using the black box method. Unit testing and validation get 100% valid results from the tested functionality. And based on the results of the system testing carried out, it can be concluded that the web-based printing management information system developed is in accordance with the functionality of the system.